2018
DOI: 10.1139/apnm-2017-0577
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and weight loss, not always a happy marriage: single blind exercise trials in females with diverse BMI

Abstract: 23Individuals show high variability in body weight responses to exercise training. Expectations and 24 motivation towards effects of exercise on body weight might influence eating behaviour and could 25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Of these, 799 abstracts and titles were reviewed, 726 articles were deleted, and 73 full-text articles were assessed for eligibility. Finally, 45 studies [ 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] met the inclusion and exclusion criteria, including 58 experimental groups ( n = 897 participants) and 34 control groups ( n = 474 participants) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 799 abstracts and titles were reviewed, 726 articles were deleted, and 73 full-text articles were assessed for eligibility. Finally, 45 studies [ 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] met the inclusion and exclusion criteria, including 58 experimental groups ( n = 897 participants) and 34 control groups ( n = 474 participants) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This single blinded randomised parallel study was conducted on healthy overweight females with BMI >25 kg/m 2…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Increasing exercise is important in obesity reduction strategies, inducing negative energy balance driven by increasing energy expenditure [1]. However, the effectiveness of exercise induced weight loss in the absence of caloric restriction remains controversial and is highly individual [2][3][4][5]. In healthy overweight women, who participated in 7 week-endurance-type exercise programme and achieved variable changes in fat mass and fat oxidation, energy expenditure and the change in resting fat oxidation were the only statistically significant independent predictors of change in fat mass [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Franz et al [143] in their meta-analysis found an average of 5% to 9% weight loss during the first 6 months of interventions based on low calorie diets, combined or not with orlistat or sibutramine, but the weight losses observed tended to plateau after 6 months, and in several instances were not maintained. Additionally, although paramount for improvement in body composition and overall health, various research groups have independently found very similar results: physical activity only has very little effect on BMI [144,145]. The overall consensus amongst practitioners is that the triad physical activity + dietary improvement + weight loss medication is much more effective than any of these strategies alone for long term, maintained weight loss.…”
Section: Therapy Of Obesity: Open Questions About Melatonin Supplementation As a Possible Toolmentioning
confidence: 99%